Prospects for Regional Cooperation between Latin America and the Caribbean Region and the Asia and Pacific Region: Perspective from East Asia - Erlinda M. Medalla; Jenny D. Balboa (Philippine Institute for Development Studies (PIDS), 2010)
The Asia and Pacific region and Latin American and Caribbean region are two regions divided not only by vast geographic distance, but also by disparities in economics, politics, culture, and history. Most recently, a number of forums explored the possibility of closing such gaps and linking the two regions through various trade and investment initiatives. The opportunities for cooperation abound and could touch on areas that will improve the regional value chain and enhance the innovation and competitiveness of both regions. Interregional cooperation could also help the two regions seek ways to deal with the current global economic crisis through a range of opportunities to stimulate the economy. This paper explores the potential for regional cooperation between the Asia and Pacific region and Latin America and the Caribbean. It also provides some recommendations to enhance the economic partnership of the two regions.
Keywords: 330; regional cooperation; Philippines; Latin America; economic partnership; East Asia; Asian regionalism; Caribbean; free trade agreements (FTAs); Regionale Wirtschaftsintegration; Freihandelszone; Lateinamerika; Karibische Staaten; Asiatisch-pazifischer Raum